Liquid for liquid marble, liquid marble, method and device for producing liquid marble, and bioreactor

JP7635513B2Active Publication Date: 2025-02-26RICOH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2020131171
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-31
Publication Date
2025-02-26
Estimated Expiration
2040-07-31

AI Technical Summary

Benefits of technology

【0009】 本発明によると、有価物産生効率が高く、種々の液体に対する、液滴の合一を抑制し、外力に対する耐久性に優れるリキッドマーブル用液体を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635513000030
    Figure 0007635513000030
  • Figure 0007635513000031
    Figure 0007635513000031
  • Figure 0007635513000001
    Figure 0007635513000001
Patent Text Reader

Abstract

To provide a liquid for liquid marbles that has high production efficiency of valuable material, suppresses the union of droplets for a variety of liquids, and has excellent durability against external force.SOLUTION: A liquid for liquid marbles has a biocatalyst, water, and a thickener, the content of the water being 15 mass% or more and 98 mass% or less, and the viscosity at 25°C being 400 mPa s or more and 4,000 mPa s or less.SELECTED DRAWING: Figure 1A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid for liquid marble, liquid marble, a method and apparatus for producing liquid marble, and a bioreactor. [Background technology]

[0002] A bioreactor generally means a device that utilizes biological reactions caused by biocatalysts such as enzymes. Immobilized enzymes, immobilized microorganisms, and other living cells are used in the biological reactions used in bioreactors. Bioreactors are used for the production of amino acids, peptide organic acids, and the isomerization of sugars. Bioreactors that utilize enzyme catalysts are also applied to some processes in the petrochemical industry. Furthermore, some bioreactors are used for analytical purposes such as various diagnoses. Many bioreactors are large devices that are difficult to carry and many of them are complicated to handle. Therefore, there is a demand for small, easy-to-use bioreactors.

[0003] Industrially used materials can be stably handled in any of the gas, liquid, and solid phases by changing the pressure and temperature. However, from the viewpoint of handling such as transportation and conveyance of materials, gas requires measures to prevent leakage and is difficult to handle efficiently due to its low density. Liquid requires measures to prevent leakage and is difficult to handle efficiently because it contaminates the conveyance route. Therefore, it is preferable to handle materials in a solid state. In the prior art, for example, a method is known in which gas or liquid is cooled and solidified, or gas or liquid is adsorbed to a porous material to handle it as a solid, but energy is required for cooling, which limits the range of industrial use.

[0004] In recent years, as a technique for handling materials without changing their phase, for example, liquid marbles produced by aphids have attracted attention. Aphids are known to cover the surface of droplets of nectar secreted from their bodies with hydrophobic particles and move them out of the nest, and are known to handle liquids as if they were solids (for example, see Non-Patent Document 1).

[0005] On the other hand, generally, the process of producing valuable products using microorganisms is carried out in a large culture tank under strict management of the culture solution. However, such a culture device requires appropriate stirring and gas supply such as oxygen, which makes the process and management complicated. In addition, the death of microorganisms in the large culture tank may induce the death of surrounding microorganisms, resulting in failure of substance production.

[0006] As an example of a liquid marble formation technology that mimics liquid marbles and has been applied industrially, a technology has been reported in which liquid droplets are encapsulated within particles, and the encapsulated droplets contain biocatalysts such as microorganisms, thereby cultivating microorganisms inside the liquid-encapsulated particles (see, for example, non-patent document 2). Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention aims to provide a liquid for liquid marbles that has high efficiency in producing valuable materials, suppresses the coalescence of droplets of various liquids, and has excellent durability against external forces. [Means for solving the problem]

[0008] As a means for solving the problems, the liquid for liquid marble of the present invention contains a biocatalyst, water, and a thickener, the water content is 15% by mass or more and 98% by mass or less, and the viscosity at 25°C is 400 mPa·s or more and 4,000 mPa·s or less. Effect of the Invention

[0009] According to the present invention, it is possible to provide a liquid for liquid marbles that has high efficiency in producing valuable materials, suppresses the coalescence of droplets for various liquids, and has excellent durability against external forces. [Brief description of the drawings]

[0010] [Figure 1A] FIG. 1A is a schematic diagram showing an example of a composite particle. [Figure 1B] FIG. 1B is a schematic diagram showing an example of a cross section in the XZ plane in FIG. 1A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] (Liquid for liquid marble) The liquid for liquid marble of the present invention contains a biocatalyst, water, and a thickener, and further contains other ingredients as necessary. The liquid for liquid marble of the present invention contains a biocatalyst, water, and a thickener, the water content is 15% by mass or more and 98% by mass or less, and the viscosity at 25°C is 400 mPa·s or more and 4,000 mPa·s or less.

[0012] Conventional techniques for culturing microorganisms using particles containing liquid have problems, such as the particles being several millimeters or larger in size, low durability (strength), and prone to coalescence, making it difficult to handle a large number of particles in the same system. In addition, the large size of the particles used makes it difficult to mix and supply gas to circulate the liquid inside the particles.

[0013] The inventors therefore investigated liquids for liquid marbles that have high efficiency in producing valuable materials, suppress the coalescence of droplets in various liquids, and have excellent durability against external forces, and have arrived at the following findings.

[0014] Liquid marbles are formed when the "hydrophilic" and "hydrophobic" properties of the liquid and solid particles are reversed. Therefore, even if the liquid is hydrophobic, liquid marbles can be formed as long as the solid particles are hydrophilic. Usually, there are no materials that can maintain hydrophilicity, and they become hydrophobic over time. This is due to the deterioration of the material itself and the adsorption of impurities. On the other hand, it is not known that the hydrophobicity of hydrophobic materials becomes hydrophilic over time. It is thought that both dirt and deterioration progress in the hydrophobic direction. Therefore, liquid marbles have usually been used in a system in which the liquid is hydrophilic and the solid particles are hydrophobic. From the viewpoint of hydrophilicity and hydrophobicity, it is preferable that the liquid is as hydrophilic as possible, and ideally it is 100% water. However, it has been found that 100% water has problems such as low viscosity and weakness to external forces. There has been no knowledge at all about the physical properties of a liquid that can achieve both biocatalytic activity and an environment in which liquid marbles can be maintained.

[0015] Therefore, the inventors discovered that by making the liquid for liquid marbles contain a biocatalyst, water, and a thickener, with the water content being between 15% and 98% by mass, and with a viscosity at 25°C of between 400 mPa·s and 4,000 mPa·s, the efficiency of valuable resource production is high, droplet coalescence is suppressed for various liquids, and excellent durability against external forces is achieved.

[0016] The viscosity of the liquid for liquid marble at 25°C is 400 mPa·s or more and 4,000 mPa·s or less, preferably 500 mPa·s or more and 3,000 mPa·s or less, and more preferably 1,000 mPa·s or more and 2,000 mPa·s or less. If the viscosity at 25°C is less than 400 mPa·s, the coalescence of the droplets cannot be suppressed, and not only will the durability of the liquid marble against external forces be reduced, but it may be impossible to produce liquid marbles. If the viscosity exceeds 4,000 mPa·s, it may be difficult to produce droplets, and it may be impossible to produce liquid marbles. On the other hand, if the viscosity at 25°C is 400 mPa·s or more and 4,000 mPa·s or less, it is advantageous in that the coalescence of the droplets can be suppressed and the durability of the liquid marble against external forces is excellent.

[0017] <Biocatalyst> The biocatalyst is not particularly limited as long as it is a living organism itself or a catalyst derived from a living organism and can change the reaction rate when a substance is converted into a different substance, and can be selected appropriately depending on the purpose. Examples of the living organism include animal cells, plant cells, and microorganisms. Examples of the biologically derived catalyst include proteins, enzymes, organelles, hormone receptors, and antibodies. These may be used alone or in combination of two or more. Among these, the biocatalyst is preferably one that can be produced using a biocatalyst. The biocatalyst to be used may be one extracted from nature, may be one synthesized, or may be a commercially available product.

[0018] The valuable product is not particularly limited as long as it can be produced using a biocatalyst and can be appropriately selected depending on the purpose. Examples of the valuable product include ethanol, acetic acid, lactic acid, butyric acid, propionic acid, and formic acid.

[0019] The content of the biocatalyst is not particularly limited and can be appropriately selected depending on the type of biocatalyst, the desired activity, and the like.

[0020] The method for measuring the catalytic activity of the biocatalyst is not particularly limited, and can be appropriately selected from known methods depending on the type of biocatalyst, the desired activity, and the like.

[0021] <Water> The water is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include pure water, tap water, well water, mineral water, hot spring water, spring water, fresh water, purified water, hot water, ion-exchanged water, physiological saline, phosphate buffer, phosphate buffered physiological saline, etc. These may be used alone or in combination of two or more.

[0022] The water content is 15% to 98% by mass, preferably 50% to 98% by mass, and more preferably 85% to 98% by mass. If the water content is less than 15% by mass, problems may occur in terms of biocatalytic activity such as microbial cultivation, and if it exceeds 98% by mass, it may become difficult to maintain viscosity. On the other hand, a water content of 15% to 98% by mass is preferable from the viewpoint of achieving a balance between the strength of the liquid marble and the production of valuable materials.

[0023] The water content in the liquid for liquid marble can be analyzed using a Karl Fischer moisture meter.

[0024] <Thickener> The thickener is not particularly limited and may be appropriately selected depending on the purpose as long as it can make the viscosity of the liquid marble liquid at 25°C 400 mPa·s or more and 4,000 mPa·s or less, and examples of the thickener include polysaccharides, synthetic resins, and derivatives thereof. These may be used alone or in combination of two or more. Among these, the thickener is preferably polysaccharides.

[0025] Examples of the polysaccharides include gums, pregelatinized or partially pregelatinized starches, dextrin, alginic acid, alginates, alginic acid esters, gelatin, seaweed extract powder, and cellulose. Examples of the gums include gum arabic, guar gum, xanthan gum, gellan gum, locust bean gum, tamarind seed gum, and psyllium seed gum. Examples of the gelatinized or partially gelatinized starches include gelatinized or partially gelatinized starches such as potato starch, corn starch, tapioca starch, rice starch, wheat starch, and sweet potato starch. Examples of the cellulose include hydroxypropyl cellulose (HPC), hydroxypropylmethyl cellulose (HPMC), methyl cellulose (MC), hydroxymethyl cellulose (HMC), carboxymethyl cellulose (CMC), hydroxyethyl cellulose (HEC), and fermented cellulose. The polysaccharides to be used may be purified, or may contain the polysaccharides, such as honey.

[0026] Examples of the synthetic resin include polyvinylpyrrolidone (PVP) and polyvinyl alcohol (PVA).

[0027] The content of the thickener is not particularly limited and can be appropriately selected depending on the purpose as long as the viscosity of the liquid marble liquid at 25°C is 400 mPa·s or more and 4,000 mPa·s or less, but is preferably 0.1% by mass or more, and more preferably 0.1% by mass or more and 10% by mass or less, based on the total amount of the liquid marble liquid. If the content of the thickener is less than 0.1% by mass, it may not be possible to achieve a viscosity of 400 mPa·s or more at 25°C. On the other hand, if the content of the thickener is 0.1% by mass or more, it is preferable in that coalescence of droplets can be suppressed and the liquid marble has excellent durability against external forces.

[0028] The content of the thickener in the liquid for liquid marble can be measured by liquid chromatography, NMR analysis, mass spectrometry, elemental analysis, and the like, either alone or in combination.

[0029] <Other ingredients> The other components in the liquid for liquid marble are not particularly limited as long as they can achieve the effects of the present invention, and can be appropriately selected depending on the purpose, but it is preferable that the liquid contains components necessary for the catalytic activity of the biocatalyst, such as additives (e.g., pH adjusters, preservatives), physiologically active substances, water-soluble compounds, water-insoluble compounds, etc. These may be used alone or in combination of two or more.

[0030] Examples of the additives include antioxidants such as sodium L-ascorbate, and antifungal agents.

[0031] Examples of the physiologically active substances include vitamins such as vitamin B1 and folic acid; amino acids such as arginine and alanine; nitrogen sources such as soybean flour, wheat germ, rolled oats, peptone, cottonseed meal, yeast extract, meat extract, corn steep liquor, ammonium sulfate, sodium nitrate, and urea; carbon sources such as carbohydrates and fats such as tomato paste, glycerin, starch, glucose, galactose, dextrin, Bacto (registered trademark) soytone, glucose, and sucrose; inorganic salts such as salt and calcium carbonate; serum such as fetal bovine serum (BSA); and growth regulators such as auxin and kinetin.

[0032] Examples of the water-soluble compound include glucose, ascorbic acid, Japanese Pharmacopoeia honey, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate ([EMIM][CF3SO3]), 1-butyl-3-methylimidazolium trifluoromethanesulfonate ([BMIM][CF3SO3]), (1-butyl-3-methylimidazolium chloride ([BMIM][Cl]), glycerin, polyglycerin, and lactose.

[0033] Examples of the water-insoluble compound include inorganic fillers such as titanium oxide, activated carbon, zeolite, and silica.

[0034] The content of the other components in the liquid for liquid marble is not particularly limited as long as the effects of the present invention can be achieved, and can be appropriately selected depending on the purpose.

[0035] (Liquid Marble) The liquid marble of the present invention is obtained by encapsulating the liquid for liquid marble of the present invention between externally added particles. The liquid marble refers to particles in a state in which the surface of the liquid for liquid marble is coated with the external particles. Therefore, in this specification, "liquid for liquid marble encapsulated with external particles" is synonymous with "a state in which the surface of the liquid for liquid marble is coated with external particles." There are no particular limitations on the liquid marble as long as it is coated to an extent that the effects of the present invention can be achieved; the surface of the liquid for the liquid marble may be completely or partially coated with the external particles.

[0036] The liquid marble contains a liquid for liquid marble and an external additive, and further contains other components as required.

[0037] <Liquid for liquid marble> The liquid for liquid marble is the liquid for liquid marble of the present invention described above, and contains a biocatalyst, water, and a thickener, and may further contain other components as necessary. The properties of the biocatalyst, the water, and the thickener are as described in the "(Liquid for Liquid Marble)" section above.

[0038] The water content in the liquid for liquid marble can be determined by collecting a number of liquid marbles, centrifuging them to separate them into external particles and encapsulated liquid (the liquid for liquid marble), and then analyzing the encapsulated liquid with a Karl Fischer moisture meter.

[0039] The content of the thickener in the liquid for liquid marble can be measured by collecting multiple liquid marbles, centrifuging them to separate them into external particles and encapsulated liquid (the liquid for liquid marble), and then subjecting the encapsulated liquid to liquid chromatography, NMR analysis, mass spectrometry, elemental analysis, etc., either alone or in combination.

[0040] <Externally added particles> The external particles are not particularly limited and can be appropriately selected according to the purpose, and examples thereof include composite particles containing two kinds of hydrophobic materials, composite particles containing an amphipathic material and a hydrophobic material, etc. These may be used alone or in combination of two or more kinds. Among these, composite particles containing two kinds of hydrophobic materials and composite particles containing an amphipathic material and a hydrophobic material are preferred in that they suppress the coalescence of droplets and have excellent durability against external forces.

[0041] The number average particle diameter d50e of the external particles is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 nm to 10 μm, more preferably 500 nm to 5 μm. When the number average particle diameter d50e of the external particles is 1 nm to 10 μm, the amount of the external particles adsorbed to the droplets of the liquid for liquid marble can be increased, and the liquid for liquid marble can be stabilized. The number-average particle diameter d50e of the external particles is the average value of the longest diameters of 10 particles arbitrarily selected in a scanning electron microscope image of the external particles observed in bulk.

[0042] The inventors discovered that if liquid marbles are made only with large particles, the contact area between the particles covering the droplets of liquid marble liquid and the droplets becomes small, resulting in exposed areas of the droplets, which results in a very weak strength against external forces and makes it difficult to improve durability. They also discovered that producing liquid marbles using only small particles improves durability against external forces, but makes them more susceptible to deformation and can cause the liquid marbles to coalesce together due to capillary action.

[0043] Therefore, the present inventors have found that in order to suppress the coalescence of droplets, it is more preferable to use composite particles containing two types of solid particles having specific physical properties and different particle sizes (hydrophobic solid particles A having a large particle size and hydrophobic solid particles B having a small particle size) in order to suppress the coalescence of liquid marbles. Furthermore, the present inventors have found that by disposing the hydrophobic solid particles B on the surfaces of the hydrophobic solid particles A to form composite particles, it is possible to further suppress the coalescence of liquid marbles, to coat the surfaces of droplets of a wider variety of liquids, and to form liquid marbles with superior durability.

[0044] <<Composite particles>> The composite particles contain hydrophobic solid particles A and hydrophobic solid particles B, and preferably further contain solid particles C, and further contain other components as necessary. The composite particle further has hydrophobic solid particles B on the surface of the hydrophobic solid particles A, the hydrophobic solid particles A having a contact angle with water CAa of 110° or more and 180° or less, the hydrophobic solid particles B having a contact angle with water CAb of 110° or more and 180° or less, the ratio (d50a / d50b) of the number average particle diameter d50a of the hydrophobic solid particles A to the number average particle diameter d50b of the hydrophobic solid particles B is 10 or more and 100 or less, and the coverage CR2 represented by the following formula 2 is 50% or more and 500% or less.

number

[0045] The composite particle further has solid particles C on the surface of the hydrophobic solid particles A, and it is preferable that the hydrophobic solid particles A have a contact angle CAa with water of 110° or more and 180° or less, the solid particles C have a contact angle CAc1 with water of less than 110°, and the solid particles C have a contact angle CAc2 with n-hexane of less than 110°, the ratio (d50a / d50c) of the number average particle diameter d50a of the hydrophobic solid particles A to the number average particle diameter d50c of the solid particles C is 10 or more and 100 or less, and the coverage CR1 represented by the following formula 1 is 0.3% or more and 18% or less.

number

[0046] -Hydrophobic solid particles A- The contact angle CAa of the hydrophobic solid particles A with water is 110° or more and 180° or less. If the contact angle CAa of the hydrophobic solid particles A with water is less than 110°, the liquid marbles are difficult to form and may coalesce. On the other hand, if the contact angle CAa of the hydrophobic solid particles A with water is 110° or more and 180° or less, coalescence of the liquid marbles can be suppressed. In this specification, "hydrophobic" means that the contact angle with water (CAa or CAb) measured by the contact angle measurement method described below is 110° or more and 180° or less.

[0047] The contact angle CAa of the hydrophobic solid particle A with water can be measured according to a conventionally known method for measuring contact angles (θ / 2 method). Specifically, a plate-like body obtained by hot pressing the constituent material of the hydrophobic solid particle A or a plate-like body obtained by casting a dispersion of the constituent material of the hydrophobic solid particle A on a substrate by a casting method is used as a measurement sample, and the angle formed between the liquid level when 10 μL of water is placed on the plate-like body using a microsyringe and the surface of the plate-like body can be measured as the contact angle CAa with water.

[0048] The conditions for the hot pressing of the constituent material of the hydrophobic solid particles A to produce a plate-like body are as follows: [Heat press conditions] · Temperature: 200℃ Total pressure: 30kN Time: 5 minutes from reaching 30kN · Work content: Fill the sample (constituent material of hydrophobic solid particle A) powder into a powder molding die (depth: 20 mm) with an inner diameter (φ) of 10 mm until the height from the bottom is 10 mm, and set it in a press machine (device name: SA-302 benchtop test press, manufacturer: Tester Sangyo Co., Ltd.). After confirming that the die has reached the specified temperature (200°C), start pressing and press up to the specified pressure (30 kN). Once the specified pressure has been reached, press for 5 minutes to create a sample (plate) for measuring the contact angle.

[0049] The plate-like body obtained by casting the dispersion liquid of the constituent material of the hydrophobic solid particle A on a substrate by a casting method can be obtained by hot pressing the constituent material of the hydrophobic solid particle A, by first placing a PTFE (polytetrafluoroethylene, average thickness: 200 μm) punched to a diameter of 10 mm in the powder molding die, scattering the powder of the sample (constituent material of the hydrophobic solid particle A) almost uniformly thereon, and then performing the hot pressing.

[0050] The method for uniformly spreading the sample (constituent material of hydrophobic solid particles A) powder is not particularly limited and may be appropriately selected depending on the purpose. Examples of the method include spreading a dry sample powder and spreading a sample dispersion liquid. The solvent used in the sample dispersion is not particularly limited and can be appropriately selected depending on the purpose, and examples of the solvent include ethanol, etc. By using the sample dispersion, it is possible to easily handle a sample having a low bulk density.

[0051] When the hydrophobic solid particles A as a constituent material of the composite particles are used as a measurement sample, the material of the hydrophobic solid particles A in the composite particles is identified by gas chromatography (GC-MS), nuclear magnetic resonance (NMR), infrared spectroscopy (IR) or the like to obtain the material, and the contact angle CAa with water is measured using the obtained material, or the hydrophobic solid particles A are isolated from the composite particles, and a plate-like body is produced from the isolated hydrophobic solid particles A, and the contact angle CAa between the plate-like body and water can be measured.

[0052] The method for isolating the hydrophobic solid particles A from the composite particles is not particularly limited and can be appropriately selected depending on the purpose. For example, there can be mentioned a method of adding alcohol to the composite particles and filtering the liquid in which the hydrophobic solid particles A are dispersed. The alcohol is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include ethanol, isopropanol, etc. These may be used alone or in combination of two or more. Among these, it is particularly preferable to use ethanol, since it is highly volatile and can be easily dried after filtration.

[0053] The number average particle diameter d50a of the hydrophobic solid particles A is not particularly limited as long as the effects of the present invention can be achieved and may be appropriately selected depending on the purpose, but is preferably 0.1 μm to 10 μm, more preferably 0.5 μm to 5 μm. When the number average particle diameter d50a of the hydrophobic solid particles A is 0.1 μm to 10 μm, the amount of the hydrophobic solid particles A adsorbed to the droplets of the liquid for liquid marble can be increased, and the liquid for liquid marble can be more stabilized. The number average particle diameter d50a of the hydrophobic solid particles A is the average value of the longest diameters of 10 particles arbitrarily selected in a scanning electron microscope image obtained by observing the hydrophobic solid particles A isolated by the above-mentioned method in bulk.

[0054] The material of the hydrophobic solid particles A is not particularly limited as long as the contact angle CAa of the hydrophobic solid particles A with water is 110° or more and 180° or less, and can be appropriately selected depending on the purpose, and examples thereof include organic materials, inorganic materials, etc. These may be used alone or in combination of two or more kinds.

[0055] The organic material may be, for example, a polymer material. The polymer material may be, for example, a resin. Examples of the resin include fluororesin, silicone resin, cellulose, and copolymers containing at least one resin selected from these. Examples of the fluororesin include polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), perfluoroethylenepropene copolymer (FEP), ethylenetetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), and ethylenechlorotrifluoroethylene copolymer (ECTFE). Examples of the silicone resin include methyl silicone resin and urethane-modified silicone resin.

[0056] Examples of the inorganic material include silica and calcium carbonate. Examples of the silica include fumed silica and spherical silica particles (QSG series: manufactured by Shin-Etsu Chemical Co., Ltd.).

[0057] The organic material and the inorganic material may further have a hydrophobic surface. Even if the organic material and the inorganic material do not have hydrophobic properties as a physical property of the material, the organic material and the inorganic material may have a hydrophobic surface by the hydrophobic treatment.

[0058] Examples of the hydrophobized organic material include hydrophobized starch, etc. Examples of the hydrophobized starch include aluminum octenyl succinate corn starch ester (trade name: Octie, manufactured by Nippon Starch Chemical Co., Ltd.). The fact that the organic material has been rendered hydrophobic can be confirmed by measuring the contact angle. The contact angle of a sample compression molded (such as by hot pressing) by the above-mentioned method is measured, and it can be confirmed that the organic material has been rendered hydrophobic by confirming that the contact angle with water is 110° or more.

[0059] Examples of the hydrophobized inorganic material include calcium carbonate treated with stearic acid, etc. Examples of the calcium carbonate treated with stearic acid include calcium carbonate (100 g), stearic acid (10 g), and methanol (500 mL) mixed together, and then the methanol is removed by distillation under reduced pressure, followed by heating and drying at 50°C. The hydrophobicity of the inorganic material can be confirmed by measuring the contact angle. For example, when the inorganic material is hydrophobized by stearic acid treatment, the contact angle of a compression molded (heat pressed, etc.) sample is measured, and the contact angle with water is confirmed to be 110° or more, thereby confirming that the inorganic material is stearic acid treated.

[0060] The shape of the hydrophobic solid particles A is not particularly limited as long as the effects of the present invention can be achieved, and may be appropriately selected depending on the purpose. Examples of the shape include spherical, true spherical, flat, acicular, columnar, irregular, rectangular, etc.

[0061] The structure of the hydrophobic solid particles A is not particularly limited as long as the effects of the present invention can be achieved, and may be appropriately selected depending on the purpose. Examples of the structure include porous, hollow, and layered.

[0062] -Hydrophobic solid particles B- The hydrophobic solid particles B are present on the surfaces of the hydrophobic solid particles A and cover the surfaces of the hydrophobic solid particles A. In this specification, the term "the hydrophobic solid particles B covers the surfaces of the hydrophobic solid particles A" is not particularly limited as long as the hydrophobic solid particles B can cover the surfaces of the hydrophobic solid particles A to an extent that the effects of the present invention can be exhibited, and it is preferable that the hydrophobic solid particles B cover the surfaces of the hydrophobic solid particles A to an extent that the coverage ratio CR2 described later is satisfied. In this specification, the term "surface of hydrophobic solid particle A" means the exposed surface of hydrophobic solid particle A.

[0063] The contact angle CAb of the hydrophobic solid particles B with water is 110° or more and 180° or less. If the contact angle CAb of the hydrophobic solid particles B with water is less than 110°, the liquid marbles are difficult to form and may coalesce. On the other hand, if the contact angle CAb of the hydrophobic solid particles B with water is 110° or more and 180° or less, coalescence of the liquid marbles can be effectively suppressed.

[0064] The contact angle CAb of the hydrophobic solid particle B with water can be measured in accordance with a conventionally known method for measuring a contact angle (θ / 2 method) in the same manner as the contact angle CAa of the hydrophobic solid particle A with water. Specifically, a plate-like body obtained by hot pressing the constituent material of the hydrophobic solid particle B or a plate-like body obtained by casting a dispersion of the constituent material of the hydrophobic solid particle B on a substrate by a casting method is used as a measurement sample, and the angle formed between the liquid level when 10 μL of water is placed on the plate-like body using a microsyringe and the surface of the plate-like body can be measured as the contact angle CAb with water.

[0065] The methods for producing the plate-like body obtained by hot pressing the constituent material of the hydrophobic solid particles B and the plate-like body obtained by casting a dispersion of the constituent material of the hydrophobic solid particles B on a substrate by a casting method are the same as those for the hydrophobic solid particles A. Furthermore, the method for measuring the contact angle CAb when the hydrophobic solid particle B, which is a constituent material of the composite particle, is used as a measurement sample and the method for isolating the hydrophobic solid particle B from the composite particle are also the same as those for the hydrophobic solid particle A.

[0066] The number average particle diameter d50b of the hydrophobic solid particles B is not particularly limited as long as the effects of the present invention can be achieved and may be appropriately selected depending on the purpose, but is preferably 0.01 μm or more and 0.5 μm or less, and more preferably 0.01 μm or more and 0.05 μm or less. When the number average particle diameter d50b of the hydrophobic solid particles B is 0.01 μm or more and 0.5 μm or less, the amount of the hydrophobic solid particles B adsorbed on the droplets of the liquid for liquid marbles can be increased, and the liquid marbles can be more stabilized. The number average particle diameter d50b of the hydrophobic solid particles B is the average value of the longest diameters of 10 particles arbitrarily selected in a scanning electron microscope image obtained by observing the hydrophobic solid particles B isolated by the above-mentioned method in bulk.

[0067] The ratio (d50a / d50b) of the number average particle diameter d50a of the hydrophobic solid particles A to the number average particle diameter d50b of the hydrophobic solid particles B (also referred to as the "particle diameter ratio (d50a / d50b)") is not particularly limited and may be appropriately selected depending on the purpose, but is preferably 10 to 100, more preferably 10 to 30. If the ratio (d50a / d50b) is less than 10, it may be difficult to form composite particles, and if the ratio (d50a / d50b) exceeds 100, it may be difficult to stably produce the liquid marbles, although composite particles can be formed. On the other hand, if the ratio (d50a / d50b) is 10 to 100, it is advantageous in that liquid marbles having excellent coalescence suppression properties and durability against external forces can be formed.

[0068] The material of the hydrophobic solid particles B is not particularly limited as long as the contact angle CAb of the hydrophobic solid particles B with water is in the range of 110° to 180°, and may be appropriately selected depending on the purpose, and examples of the material include organic materials, inorganic materials, etc. These may be used alone or in combination of two or more.

[0069] The organic material may be, for example, a polymer material. The polymer material may be, for example, a resin. Examples of the resin include fluororesin, silicone resin, cellulose, and copolymers containing at least one resin selected from these. Examples of the fluororesin include polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), perfluoroethylenepropene copolymer (FEP), ethylenetetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), and ethylenechlorotrifluoroethylene copolymer (ECTFE). Examples of the silicone resin include methyl silicone resin and urethane-modified silicone resin.

[0070] Examples of the inorganic material include silica and calcium carbonate. Examples of the silica include fumed silica and spherical silica particles (QSG series: manufactured by Shin-Etsu Chemical Co., Ltd.).

[0071] The organic material and the inorganic material may further have a hydrophobic surface. Even if the organic material and the inorganic material do not have hydrophobic properties as a physical property of the material, the organic material and the inorganic material may have a hydrophobic surface by the hydrophobic treatment. The hydrophobized organic material and the hydrophobized inorganic material can be the same as those mentioned above for the hydrophobic solid particles A, and the method for confirming that the organic material and the inorganic material have been hydrophobized can be the same as those mentioned above for the hydrophobic solid particles A.

[0072] The shape of the hydrophobic solid particles B is not particularly limited as long as the effects of the present invention can be achieved, and may be appropriately selected depending on the purpose. Examples of the shape include spherical, true spherical, flat, acicular, columnar, irregular, rectangular, etc.

[0073] The structure of the hydrophobic solid particles B is not particularly limited as long as the effects of the present invention can be achieved, and may be appropriately selected depending on the purpose. Examples of the structure include porous, hollow, and layered.

[0074] The material, shape or structure of the hydrophobic solid particles B may be the same as or different from that of the hydrophobic solid particles A as long as the effects of the present invention are achieved. However, it is preferred that at least one of the hydrophobic solid particles A and the hydrophobic solid particles B is at least one of a fluororesin, silica, stearic acid-treated calcium carbonate and hydrophobized starch.

[0075] The coverage CR2 of the composite particle, represented by the following formula 2, is not particularly limited and may be appropriately selected depending on the purpose as long as the effects of the present invention can be achieved, but is preferably 50% to 500%, and more preferably 100% to 200%. If the coverage CR2 is less than 50%, the hydrophobic solid particles A will be predominant in contact with water, making it difficult to obtain the coalescence suppression effect, while if the coverage CR2 exceeds 500%, the hydrophobic solid particles B will be aggregated and deposited on the surface of the hydrophobic solid particles A, making it difficult to obtain the coalescence suppression effect, since the hydrophobic solid particles B will be predominant in contact with water. On the other hand, if the coverage CR2 is 50% to 500%, it is preferable in that the liquid marble having excellent coalescence suppression properties and durability against external forces can be formed.

number

[0076] The mass (g) and the volume (μm 3 ) may be per unit particle, or may be per bulk if the mass and volume of the composite particles used are based on the same standard. The volume of each particle may be the average volume of the particles used, or the volume calculated assuming that the particle is a perfect sphere with the number-average particle diameter obtained may be used. The covering ratio CR2 means the ratio of the hydrophobic solid particles B present on the surface of the hydrophobic solid particles A.

[0077] The coverage ratio CR2 is calculated as follows. First, when the composite particle is a true sphere (the hydrophobic solid particle A and the hydrophobic solid particle B are also true spheres), the sum of the number average particle diameter d50a of the hydrophobic solid particle A and the number average particle diameter d50b of the hydrophobic solid particle B divided by 2 (d50a / 2+d50b / 2) is defined as the radius of the composite particle, and the surface area of ​​the composite particle (4π(d50a / 2+d50b / 2) 2 ) is calculated. Next, the area of ​​the hydrophobic solid particles B covering the surface of the hydrophobic solid particle A is calculated by multiplying the area of ​​a cross section of the hydrophobic solid particle B, which is perpendicular to a line segment connecting the center of one of the hydrophobic solid particles A and the center of the hydrophobic solid particle B, including the center of the hydrophobic solid particle B (hereinafter referred to as the cross-sectional area Sb), by the number of the hydrophobic solid particles B covering one of the hydrophobic solid particles A. Note that the cross-sectional area Sb can be calculated by using the number-average particle diameter d50b of the hydrophobic solid particles B and multiplying it by π(d50b / 2) 2 The number of the hydrophobic solid particles B covering one of the hydrophobic solid particles A can be expressed as follows, using the mass Xa, density Ya, and volume Za of the hydrophobic solid particle A, and the mass Xb, density Yb, and volume Zb of the hydrophobic solid particle B: {Xb(g) / Yb(g / μm 3 ) / Zb(g / μm 3 )} / {Xa(g) / Ya(g / μm 3 ) / Za(g / μm 3 )}.

[0078] Fig. 1A is a schematic diagram showing an example of the composite particle, and Fig. 1B is a schematic diagram showing an example of a cross section in the XZ plane in Fig. 1A. As shown in Fig. 1A, the composite particle 10 of the present invention contains hydrophobic solid particles A11 and hydrophobic solid particles B12, and the hydrophobic solid particles B12 cover the surface of the hydrophobic solid particles A11. When calculating the coverage ratio CR1, the surface area of ​​the composite particle 10 is calculated from the number average particle diameter d50a of the hydrophobic solid particles A11 and the number average particle diameter d50b of the hydrophobic solid particles B12, and the coverage ratio CR1 is calculated as the ratio of the area occupied by the hydrophobic solid particles B12 to the surface area of ​​the composite particle 10. The area occupied by the hydrophobic solid particles B12 is calculated by multiplying the cross-sectional area Sb of the hydrophobic solid particles B12, which is perpendicular to the line segment connecting the center of the hydrophobic solid particles A11 and the center of the hydrophobic solid particles B12 and includes the center of the hydrophobic solid particles B12, by the number of hydrophobic solid particles B12 covering one hydrophobic solid particle A11, as shown in Fig. 1B.

[0079] -Solid particle C- The solid particles C are present on the surfaces of the hydrophobic solid particles A and, together with the hydrophobic solid particles B, cover the surfaces of the hydrophobic solid particles A. In this specification, the term "the solid particles C and the hydrophobic solid particles B cover the surfaces of the hydrophobic solid particles A" is not particularly limited as long as the solid particles C and the hydrophobic solid particles B can cover the surfaces of the hydrophobic solid particles A to an extent that the effects of the present invention can be exhibited. It is preferable that the solid particles C and the hydrophobic solid particles B cover the surfaces of the hydrophobic solid particles A to an extent that the effects of the present invention can be exhibited.

[0080] The inventors have found that when liquid marbles coated with composite particles made of only hydrophobic materials are used in water, they float on the water surface and are unable to maintain their shape. In order to produce valuable products from the biocatalyst, it may be desirable to be able to place the liquid marbles in water and maintain their shape for a long period of time.

[0081] Therefore, the present inventors have found that liquid marbles that can be used in water can be formed by adjusting the contact angle CAa of the hydrophobic solid particle A with water, the contact angle CAc1 of the solid particle C with water, and the contact angle CAc2 of the solid particle C with n-hexane to specific ranges. Therefore, when the composite particles contain the solid particles C, the liquid marbles are advantageous in that they suppress the coalescence of droplets and have excellent durability against external forces, and can also be used in water.

[0082] The contact angle CAc1 of the solid particles C with water is not particularly limited and may be appropriately selected depending on the purpose, but is preferably less than 110°. If the contact angle CAc1 of the solid particles C with water is 110° or more, the liquid marbles may float on the water surface and therefore cannot be used in water, and the liquid marbles may coalesce. On the other hand, if the contact angle CAc1 of the solid particles C with water is less than 110°, the liquid marbles can be used in water and coalescence of the liquid marbles can be suppressed.

[0083] The contact angle CAc1 of the solid particle C with water can be measured in accordance with a conventionally known method for measuring a contact angle (θ / 2 method) in the same manner as the contact angle CAa of the hydrophobic solid particle A with water. Specifically, a plate-like body obtained by hot pressing the constituent material of the solid particle C or a plate-like body obtained by casting a dispersion of the constituent material of the solid particle C on a substrate by a casting method is used as a measurement sample, and the angle formed between the liquid level when 10 μL of water is placed on the plate-like body using a microsyringe and the surface of the plate-like body can be measured as the contact angle CAc1 with water.

[0084] The contact angle CAc2 of the solid particles C with n-hexane is not particularly limited and may be appropriately selected depending on the purpose, but is preferably less than 110°. If the contact angle CAc2 of the solid particles C with n-hexane is 110° or more, the liquid marbles will float on the water surface and cannot be used in water, and will lose affinity with the hydrophobic solid particles A, causing the liquid marbles to coalesce. On the other hand, if the contact angle CAc2 of the solid particles C with n-hexane is less than 110°, the liquid marbles can be used in water, and affinity with the hydrophobic solid particles A can be ensured, preventing the liquid marbles from coalescing.

[0085] The contact angle CAc2 of the solid particle C with n-hexane can be measured in accordance with a conventionally known method for measuring a contact angle (θ / 2 method) in the same manner as the contact angle CAa of the hydrophobic solid particle A with water. Specifically, a plate-like body obtained by hot pressing the constituent material of the solid particle C or a plate-like body obtained by casting a dispersion of the constituent material of the solid particle C on a substrate by a casting method is used as a measurement sample, and the angle formed between the liquid level of 10 μL of n-hexane placed on the plate using a microsyringe and the surface of the plate can be measured as the contact angle CAc2 with water.

[0086] The methods for producing the plate-like body obtained by hot pressing the constituent material of the solid particles C and the plate-like body obtained by casting a dispersion of the constituent material of the solid particles C on a substrate by a casting method are the same as those for the hydrophobic solid particles A. Furthermore, the method for measuring the contact angle CAc when the solid particles C, which are a constituent material of the composite particles, are used as a measurement sample, and the method for isolating the solid particles C from the composite particles are also the same as in the case of the hydrophobic solid particles A.

[0087] The number average particle diameter d50c of the solid particles C is not particularly limited as long as the effects of the present invention can be achieved and can be appropriately selected depending on the purpose, but is preferably 0.01 μm to 5 μm, more preferably 0.1 μm to 1 μm. When the number average particle diameter d50c of the solid particles C is 0.01 μm to 5 μm, the amount of the solid particles C adsorbed to the droplets of the liquid for liquid marbles can be increased, and the solid particles C can be easily adsorbed to the hydrophobic solid particles A, thereby making the liquid marble more stable. The number average particle diameter d50c of the solid particles C is the average value of the longest diameters of 10 arbitrarily selected particles in a scanning electron microscope image obtained by observing the solid particles C isolated by the above-mentioned method in bulk.

[0088] The ratio (d50a / d50c) of the number average particle diameter d50a of the hydrophobic solid particles A to the number average particle diameter d50c of the solid particles C is 10 or more and 100 or less, and preferably 10 or more and 50 or less. If the ratio (d50a / d50c) is less than 10, it becomes difficult to form the composite particles, and if the ratio (d50a / d50c) exceeds 100, it becomes difficult to stably produce the liquid marbles, although the composite particles can be formed. On the other hand, if the ratio (d50a / d50c) is 10 or more and 100 or less, it is advantageous in that it is possible to form the liquid marbles that are excellent in coalescence suppression and durability against external forces and can be used in water.

[0089] The ratio (d50a / [(d50b+d50c) / 2]) of the number average particle diameter d50a of the hydrophobic solid particles A to the average value of the number average particle diameter d50b of the hydrophobic solid particles B and the number average particle diameter d50c of the solid particles C (also referred to as the "particle diameter ratio (d50a / [(d50b+d50c) / 2)") is not particularly limited and may be appropriately selected depending on the purpose, but is preferably 10 to 100, more preferably 10 to 30. If the ratio (d50a / [(d50b+d50c) / 2]) is less than 10, it may be difficult to form composite particles, and if the ratio (d50a / [(d50b+d50c) / 2]) exceeds 100, it may be difficult to stably produce the liquid marbles, although composite particles can be formed. On the other hand, when the ratio (d50a / [(d50b+d50c) / 2]) is 10 or more and 100 or less, it is advantageous in that the liquid marble can be formed with excellent coalescence suppression properties and durability against external forces.

[0090] The content (mass%) of the solid particles C relative to the total content (mass%) of the hydrophobic solid particles A and the solid particles C in the composite particles (hereinafter sometimes referred to as "content 1 of solid particles C") is not particularly limited and may be appropriately selected depending on the purpose as long as the coverage CR1 is satisfied, but is preferably 0.1 mass% or more and less than 5.5 mass%, and more preferably 0.6 mass% or more and 1.1 mass% or less. The content 1 of solid particles C can be adjusted by the amounts of the hydrophobic solid particles A and the solid particles C added when the composite particles are produced.

[0091] The content (mass%) of the solid particles C relative to the total content (mass%) of the hydrophobic solid particles A, the solid particles C, and the hydrophobic solid particles B (described later) in the composite particles is not particularly limited and may be appropriately selected depending on the purpose as long as the coverage CR1 is satisfied, but is preferably 0.1 mass% or more and less than 5 mass%, and more preferably 0.5 mass% or more and 1.0 mass% or less. The content 2 of the solid particles C can be adjusted by the amounts of the hydrophobic solid particles A, C, and B added when the composite particles are produced.

[0092] The ratio of the content 2 (mass%) of the solid particles C to the content (mass%) of the hydrophobic solid particles B (content 2 of solid particles C / content 2 of hydrophobic solid particles B) is not particularly limited and can be appropriately selected depending on the purpose, but is preferably more than 1.8 and not more than 96.0, and more preferably 9.5 to 96.0. When the ratio (content 2 of solid particles C / content 2 of hydrophobic solid particles B) is more than 1.8 and not more than 96.0, the liquid marble does not float on the water surface and can be suitably used in water. On the other hand, when it exceeds 96.0, the hydrophobic solid particles A and the solid particles C may decompose in water, and the liquid marble may not be able to maintain its shape, and when it is 1.8 or less, the liquid marble may float on the water surface and may not be usable in water.

[0093] The material of the solid particles C is not particularly limited as long as the contact angle CAc1 of the solid particles C with water is less than 110°, and the contact angle CAc2 of the solid particles C with n-hexane is less than 110°. The material can be appropriately selected depending on the purpose, and examples thereof include organic materials and inorganic materials. These may be used alone or in combination of two or more. Among these, a material having amphiphilic properties is preferable.

[0094] Examples of the organic material include hydroxypropyl cellulose, hydroxypropyl methyl cellulose, poly(N-isopropylacrylamide), polyethylene oxide, polyethylene glycol, phospholipids, etc. Among these, the organic material is preferably at least one of hydroxypropyl cellulose and hydroxypropyl methyl cellulose from the viewpoint of not inhibiting the function of the biocatalyst. The inorganic material may, for example, be calcium carbonate.

[0095] The organic material and the inorganic material may further have a surface that has been treated so that the contact angle CAc1 of the solid particle C with water is less than 110° and the contact angle CAc2 of the solid particle C with n-hexane is less than 110°. Even if the organic material and the inorganic material do not have physical properties that make the contact angle CAc1 less than 110° and the contact angle CAc2 less than 110°, the organic material and the inorganic material may be used as long as the surface treatment gives the material surface physical properties that make the contact angle CAc1 less than 110° and the contact angle CAc2 less than 110°.

[0096] An example of the surface-treated organic material is a polycarbonate resin that has been subjected to an ozone oxidation treatment.

[0097] It can be confirmed by measuring the contact angle that the organic material or the inorganic material is provided with physical properties such that the contact angle CAc1 is less than 110° and the contact angle CAc2 is less than 110°. By measuring the contact angle of a sample compression molded (such as hot pressing) by the above-mentioned method and confirming that the contact angle with water is less than 110° and the contact angle with n-hexane is less than 110°, it can be confirmed that the organic material or the inorganic material is provided with physical properties such that the contact angle CAc1 is less than 110° and the contact angle CAc2 is less than 110°.

[0098] The shape of the solid particles C is not particularly limited as long as the effects of the present invention can be achieved, and may be appropriately selected depending on the purpose. Examples of the shape include spherical, true spherical, flat, acicular, columnar, amorphous, and rectangular parallelepiped shapes.

[0099] The structure of the solid particles C is not particularly limited as long as the effects of the present invention can be achieved, and may be appropriately selected depending on the purpose. Examples of the structure include porous, hollow, and layered.

[0100] The composite particle has a coverage CR1, expressed by the following formula 1, of 0.3% to 18%, preferably 0.3% to 10%. If the coverage CR1 is less than 0.3%, the hydrophobic solid particles A will be predominant in contact with water, and when used in water, they will float on the water surface and cannot be used in water, and it will be difficult to obtain the coalescence suppression effect. If the coverage CR1 exceeds 18%, the solid particles C will be aggregated and deposited on the surface of the hydrophobic solid particles A, and the solid particles C will be predominant in contact with water, making it difficult to obtain the coalescence suppression effect, and the hydrophobic solid particles A and C will decompose in water, making it impossible to maintain the shape of the liquid marble. On the other hand, if the coverage CR1 is 0.3% to 18%, it is advantageous in that it is possible to form the liquid marble that is excellent in coalescence suppression and durability against external forces and can be used in water.

number

[0101] The mass (g) and the volume (μm 3 ) may be per unit particle, or may be per bulk if the mass and volume of the composite particles used are based on the same standard. The volume of each particle may be the average volume of the particles used, or the volume calculated assuming that the particle is a perfect sphere with the number-average particle diameter obtained may be used. The covering rate CR1 means the rate at which the solid particles C are present on the surface of the hydrophobic solid particles A.

[0102] The coverage rate CR1 is determined in the same manner as the coverage rate CR2, as follows. First, when the composite particle is a true sphere (the hydrophobic solid particle A and the solid particle C are also true spheres), the sum of the number average particle diameter d50a of the hydrophobic solid particle A and the number average particle diameter d50c of the solid particle C divided by 2 (d50a / 2+d50c / 2) is defined as the radius of the composite particle, and the surface area of ​​the composite particle (4π(d50a / 2+d50c / 2) 2 ) is calculated. Next, the area of ​​the solid particles C covering the surface of the hydrophobic solid particle A is calculated by multiplying the area of ​​a cross section of the solid particle C that is perpendicular to a line segment connecting the center of one of the hydrophobic solid particles A and the center of the solid particle C and includes the center of the solid particle C (hereinafter referred to as the "cross-sectional area Sc") by the number of the solid particles C covering one of the hydrophobic solid particles A. Note that the cross-sectional area Sc is calculated by using the number-average particle diameter d50c of the solid particles C and multiplying it by π(d50c / 2) 2The number of the solid particles C that cover one of the hydrophobic solid particles A can be expressed as follows, using the mass Xa, density Ya, and volume Za of the hydrophobic solid particle A, and the mass Xc, density Yc, and volume Zc of the solid particle C: {Xc(g) / Yc(g / μm 3 ) / Zc(g / μm 3 )} / {Xa(g) / Ya(g / μm 3 ) / Za(g / μm 3 )}.

[0103] The coverage CR3 of the composite particle, represented by the following formula 3, is not particularly limited, and may be appropriately selected depending on the purpose as long as the effects of the present invention can be achieved, but is preferably 50% to 518%, and more preferably 100% to 210%. If the coverage CR3 is less than 50%, the hydrophobic solid particles A will be predominant in contact with water, making it difficult to obtain the coalescence suppression effect, and if the coverage CR3 exceeds 518%, the solid particles C and the hydrophobic solid particles B will be in a state of being aggregated and deposited on the surface of the hydrophobic solid particles A, and the solid particles C and the hydrophobic solid particles B will be predominant in contact with water, making it difficult to obtain the coalescence suppression effect. On the other hand, if the coverage CR3 is 50% to 518%, it is preferable in that the liquid marble having excellent coalescence suppression properties and durability against external forces can be formed. The covering rate CR3 means the rate of the solid particles C and the hydrophobic solid particles B present on the surface of the hydrophobic solid particles A.

number

[0104] The ratio (CR2 / CR1) between the coverage rate CR1 and the coverage rate CR2 is not particularly limited and can be appropriately selected depending on the purpose, but is preferably more than 5 and not more than 300, and more preferably from 20 to 290. When the ratio (CR2 / CR1) is more than 5 and not more than 300, the liquid marble does not float on the water surface and can be suitably used in water. On the other hand, when the ratio is 5 or less, the hydrophobic solid particles A and the solid particles C may decompose in water, making it impossible for the liquid marble to maintain its shape, and when it exceeds 300, the liquid marble may float on the water surface and make it impossible to use the liquid marble in water.

[0105] -Other ingredients- The other components in the composite particles are not particularly limited and can be appropriately selected depending on the purpose. Examples of the other components include hydrophobic solid particles other than the hydrophobic solid particles A and the hydrophobic solid particles B that form the composite particles, and additives.

[0106] The hydrophobic solid particles other than the hydrophobic solid particles A and the hydrophobic solid particles B that form the composite particles are not particularly limited as long as they are hydrophobic solid particles other than the hydrophobic solid particles A and the hydrophobic solid particles B that form the composite particles and can be appropriately selected depending on the purpose. For example, hydrophobic solid particles made of the same material as the hydrophobic solid particles A and the hydrophobic solid particles B can be used.

[0107] The additives are not particularly limited as long as they can achieve the effects of the present invention, and can be appropriately selected depending on the purpose. For example, zinc stearate can be used.

[0108] The content of the other components in the composite particles is not particularly limited as long as it does not impair the effects of the present invention, and can be appropriately selected depending on the purpose.

[0109] --Method of manufacturing composite particles-- The method for producing the composite particles is not particularly limited and can be appropriately selected depending on the purpose. For example, the method includes adding the hydrophobic solid particles A, the hydrophobic solid particles B, and, if necessary, the solid particles C and the other components to a mixer under an inert gas atmosphere, and stirring at 10 rpm for 12 hours.

[0110] The method for analyzing the properties of the composite particles is not particularly limited and can be appropriately selected depending on the purpose. For example, the following methods can be mentioned. The obtained composite particles are dispersed in an alcohol (e.g., ethanol, isopropanol, etc.) to separate the hydrophobic solid particles A, C, and B, and then the hydrophobic solid particles A, C, and B are isolated by filtration. The mass (g) and density (g / μm 3 ), and volume (μm 3 ) are measured by the following methods. The mass (g) of the hydrophobic solid particles A, the solid particles C, and the hydrophobic solid particles B can be measured using a precision balance. The densities (g / μm 3 The densities (g / μm ) of the hydrophobic solid particles A, C, and B are measured values ​​of true density, and can be measured using a Gay-Lussac type pycnometer. 3 ) may be the catalog value or literature value for the solid particles used. The volumes (μm 3 ) can be calculated from the number average particle size of each individual particle.

[0111] The number average particle diameter d50a of the isolated hydrophobic solid particles A, the number average particle diameter d50c of the isolated solid particles C, and the number average particle diameter d50b of the isolated hydrophobic solid particles B can be determined by photographing the isolated hydrophobic solid particles A, C, and B using an electron microscope, and calculating the average value of the longest diameters of 10 particles arbitrarily selected from the obtained electron microscope images.

[0112] The contact angle CAa of the isolated hydrophobic solid particle A, the contact angle CAc1 and the contact angle CAc2 of the isolated solid particle C, and the contact angle CAb of the isolated hydrophobic solid particle B can be measured by heat-pressing the isolated hydrophobic solid particle A, the solid particle C, and the hydrophobic solid particle B, which are the constituent materials of the composite particle, into a plate-like body or by casting the dispersion onto a substrate to form a plate-like body, and then placing 10 μL of water or n-hexane on the sample using a microsyringe, and measuring the angle between the water or n-hexane and the smooth surface of the sample. The heat-pressing and casting methods are the same as those described above.

[0113] <Other ingredients> The other components in the liquid marble are not particularly limited and can be appropriately selected depending on the purpose. The contents of the other components are not particularly limited and can be appropriately selected depending on the purpose.

[0114] The number average particle diameter d50d of the liquid marbles is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 15 μm to 2.5 mm, more preferably 15 μm to 1.0 mm. When the number average particle diameter d50d of the liquid marbles is 15 μm or more, the drying of the liquid marbles during droplet processing can be controlled, and the liquid marbles can be produced efficiently. Furthermore, when the number average particle diameter d50d of the liquid marbles is 2.5 mm or less, the liquid marbles can be prevented from spontaneously merging or bursting due to the influence of gravity. The number-average particle size d50d of the liquid marbles is the average value of the longest diameters of 10 arbitrarily selected liquid marbles in an optical microscope image of the liquid marbles observed in bulk.

[0115] There are no particular limitations on the method for analyzing the components of the droplets contained in the liquid marble, and the method can be appropriately selected depending on the purpose. For example, a method may be used in which the liquid marble is exposed to ethanol vapor, filtered to separate the liquid marble liquid (droplets) and the composite particles, and the liquid marble liquid is then analyzed.

[0116] The method for analyzing the liquid for liquid marble is not particularly limited and can be appropriately selected from known methods depending on the purpose, and examples thereof include liquid chromatography.

[0117] (Liquid marble manufacturing method and liquid marble manufacturing device) The method for producing liquid marble of the present invention is a method for obtaining liquid marble by encapsulating the liquid for liquid marble of the present invention with external additive particles. The method for producing the liquid marbles is not particularly limited as long as the liquid for the liquid marbles can be encapsulated by the external particles, and can be appropriately selected depending on the purpose. However, it is preferable for the method to include a droplet formation process and a surface coating process, and further includes other processes as necessary.

[0118] The liquid marble manufacturing apparatus of the present invention is an apparatus for obtaining liquid marble by encapsulating the liquid for liquid marble of the present invention with external additive particles. The liquid marble manufacturing apparatus is not particularly limited as long as it can encapsulate the liquid for liquid marble with the external particles, and can be appropriately selected depending on the purpose. However, it is preferable for the apparatus to have a droplet forming means and a surface coating means, and further has other means as necessary.

[0119] The method for producing liquid marble is suitably carried out by the liquid marble production apparatus. Below, the method for producing liquid marble of the present invention will be explained together with the apparatus for producing liquid marble of the present invention.

[0120] <Droplet forming process and droplet forming means> The droplet forming step is a step of forming droplets from the liquid for liquid marble. The droplet forming means is a means for forming droplets from the liquid for liquid marble. The droplet forming step can be suitably carried out by the droplet forming means.

[0121] The liquid for liquid marble is the liquid for liquid marble of the present invention described above, and contains a biocatalyst, water, and a thickener, and may further contain other components as necessary. The properties of the biocatalyst, the water, and the thickener are as described in the "Thickener" section of the "(Liquid for Liquid Marble)" section.

[0122] The droplet forming means is not particularly limited as long as it can form droplets from the liquid for liquid marble, and can be appropriately selected from known droplet forming means according to the purpose, for example, an inkjet method, a dispenser method, a spray dry method, etc. Among these, the dispenser method is preferred because it has a wide range of properties that can be turned into droplets, is versatile, and can control the size of the droplets by the size of the hole diameter of the head and the extrusion pressure of the filling liquid.

[0123] <Surface coating process and surface coating means> The surface coating step is a step of coating the surface of the liquid for liquid marble with externally added particles having a number-average particle size of 1 nm or more and 10 μm or less. The surface coating means is a means for coating the surface of the liquid for liquid marble with externally added particles having a number-average particle size of 1 nm or more and 10 μm or less. The surface coating step can be suitably carried out by the surface coating means. In this specification, the term "surface coating" is not particularly limited as long as it is coated to an extent that the effects of the present invention can be achieved, and the surface of the droplet may be completely or partially coated with the composite particle.

[0124] <<Externally added particles>> The external particles are not particularly limited and can be appropriately selected depending on the purpose, and the same ones as those described in the "<External Particles>" section of "(Liquid Marble)" above can be used. Among these, composite particles containing two types of hydrophobic materials are preferred in that they suppress the coalescence of droplets and have excellent durability against external forces.

[0125] -Composite particles- The composite particles are not particularly limited and can be appropriately selected depending on the purpose. The same composite particles as those described in the "<<Composite Particles>>" section of "(Liquid Marble)" above can be used. In a specific example, the composite particle further comprises hydrophobic solid particles B on the surface of the hydrophobic solid particles A, the hydrophobic solid particle A has a contact angle CAa with water of 110° or more and 180° or less; the contact angle CAb of the hydrophobic solid particle B with water is 110° or more and 180° or less; the ratio (d50a / d50b) of the number average particle diameter d50a of the hydrophobic solid particles A to the number average particle diameter d50b of the hydrophobic solid particles B is 10 or more and 100 or less, The coverage CR2 represented by the following formula 2 is 50% or more and 500% or less.

number

[0126] The method of coating the surface of the droplets with the composite particles is not particularly limited as long as the droplets and the composite particles can be brought into contact with each other, and can be appropriately selected depending on the purpose, and examples of the method include a method of spraying the composite particles onto the droplets in flight, a method of disposing the droplets in a container in which the composite particles are spread, etc. Among these, the method of disposing the droplets in a container in which the composite particles are spread is preferred from the viewpoint of ease of control of the device.

[0127] In the case of the method of distributing the droplets in a container in which the composite particles are spread, it is preferable to include a step of shaking the container while supplying the composite particles to the container in order to cover the entire surface of the droplets with the composite particles after distributing the droplets in the container in which the composite particles are spread, a step of tilting the container to roll the droplets, etc. These steps may be performed alone, or any one of the steps may be performed before the other step.

[0128] A commercially available powder supplying device can be used as a means for supplying the composite particles to the container, and the mechanism and type of the powder supplying device can be appropriately selected depending on the properties of the composite particles.

[0129] -Liquid Marble- The liquid marble obtained by the surface coating step and the surface coating means is the same as the liquid marble of the present invention described above.

[0130] <Other steps and other means> The other steps are not particularly limited and can be appropriately selected depending on the purpose. Examples of the other steps include a separation step and a recovery step. The other means is not particularly limited and can be appropriately selected depending on the purpose. Examples of the other means include a separation means and a recovery means. The other step can be suitably carried out by the other step, the separation step can be suitably carried out by the separation means, and the recovery step can be suitably carried out by the recovery means. Among these, the method for producing liquid marble preferably includes the separation step, and the apparatus for producing liquid marble preferably includes the separation means.

[0131] -Separation process and separation means- The separation step is a step of separating the composite particles that have not been subjected to the surface coating in the surface coating step from the liquid marbles. The separation means is a means for separating the composite particles that have not been subjected to the surface coating by the surface coating means from the liquid marbles. The separation step can be suitably carried out by the separation means.

[0132] In the surface coating process, the method for separating the composite particles that have not been subjected to the surface coating from the liquid marbles is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include a method of picking up the liquid marbles, and a method of separating the mixture of the liquid marbles and the composite particles by utilizing the difference in specific gravity to remove the composite particles. These methods may be performed alone, or any of the methods may be performed before the other steps. Among these, the method utilizing the difference in specific gravity is preferred from the viewpoint of productivity.

[0133] An example of a method for separating the mixture of the liquid marbles and the composite particles by utilizing the difference in specific gravity and removing the composite particles is to pass the mixture through a push-pull type dust collection system.

[0134] -Recovery process and recovery means- The recovery step is a step of recovering the liquid marble separated in the separation step. The recovery means is a means for recovering the liquid marbles separated by the separation means.

[0135] The method for collecting the separated liquid marbles is not particularly limited and can be appropriately selected depending on the purpose, and may be, for example, a method of dropping the liquid marbles from the container and collecting them in a collection container. In order to cushion the impact of the drop, it is preferable to place the collection container within 200 mm from the container, and it is also preferable to tilt the collection container. It is also preferable that the collection container is corrugated, and its inner wall is hydrophobized, or made of a hydrophobic material.

[0136] (Bioreactor) The bioreactor of the present invention comprises the liquid marble of the present invention, and preferably comprises a supporting means, and further comprises other means as necessary. The bioreactor is a device that utilizes the biological reaction caused by the biocatalyst in the liquid marble.

[0137] <Supporting Means> The supporting means is a means for supporting the liquid marble. The structure and shape of the supporting means are not particularly limited as long as they are capable of supporting the liquid marbles, and can be appropriately selected depending on the purpose. When the biocatalyst requires a reaction liquid such as a culture liquid, it is preferable that the support means has a structure and shape that can be filled with the reaction liquid, and when the biocatalyst requires a reaction in the atmosphere, it is preferable that the support means has a structure and shape that can retain the atmosphere. The support means may have a function as a reaction field of the bioreactor.

[0138] <Other methods> The other means are not particularly limited and can be appropriately selected depending on the purpose. Examples of the other means include a temperature adjusting means, an oxygen and carbon dioxide concentration adjusting means, a separation means, and a recovery means.

[0139] -Temperature control means- The temperature adjusting means is a means for adjusting the temperature of the supporting means serving as the reaction field. The temperature is not particularly limited and can be appropriately selected depending on the type of the biocatalyst, the target reaction, and the like.

[0140] -Oxygen and carbon dioxide concentration means- The oxygen and carbon dioxide concentration control means is a means for controlling the oxygen concentration and the carbon dioxide concentration in the support means serving as the reaction field. The oxygen concentration and the carbon dioxide concentration are not particularly limited and can be appropriately selected depending on the type of the biocatalyst, the target reaction, and the like.

[0141] -Separation means- The separation means is a means for separating valuable materials produced from the liquid marble. The separation method is not particularly limited and can be appropriately selected depending on the type of valuable product produced, the reaction system, and the like.

[0142] -Method of recovery- The recovery means is a means for recovering valuable materials produced from the liquid marble. The valuable materials may be directly recovered from the supporting means by the recovery means, or may be separated by the separation means and then captured by the recovery means. The recovery method is not particularly limited and can be appropriately selected depending on the type of valuable product produced, the reaction system, and the like.

[0143] The bioreactor is not particularly limited as long as it can react the biocatalyst in the liquid marbles, and may be a known type of bioreactor in which the liquid marbles are introduced into a reaction field. Examples of the known bioreactors include those described in Japanese Patent No. 3283982 and Japanese Patent No. 3390377.

[0144] The uses of the bioreactor are not particularly limited as long as it can react the biocatalyst in the liquid marble, and it can be used appropriately depending on the type of substrate, etc. In addition to producing the valuable materials, it can also be suitably used for treating or purifying sewage, river water, lake water, various wastewater, excess sludge, substances that cause odors, etc. EXAMPLES

[0145] The present invention will be specifically described below with reference to Experimental Examples and Reference Examples, but the present invention is not limited to these Experimental Examples and Reference Examples.

[0146] (Experimental Example 1) -Production of Composite Particle 1- As the hydrophobic solid particle A, polytetrafluoroethylene (PTFE, number average particle diameter d50a: 1.0 μm, contact angle CAa: 120°, mass Xa: 100.0 g, density Ya: 2.20 × 10 -12 g / μm 3 , volume Za: 0.52 μm 3 , c, product name: 430935-100G), and hydrophobic silica (number average particle size d50b: 0.030 μm, contact angle CAb: 170°, mass Xb: 10.6 g, density Yb: 1.80 × 10 -12 g / μm 3 , volume Zb: 1.4×10 -5 μm 3 Using a mixture of 100% ethanol (manufactured by Shin-Etsu Chemical Co., Ltd., product name: QSG-30), the mixture was added to a V-shaped container rotary mixer (manufactured by Nishimura Machinery Works, Ltd., device name: NV-5) under inert gas (nitrogen, 25°C) and stirred at 10 rpm for 12 hours to obtain composite particles 1. The volume of each particle was calculated based on the assumption that the particle was a perfect sphere with the number-average particle size as its diameter.

[0147] -Production of Liquid 1 for Liquid Marble- A solution of water to which 0.5% by mass of yeast (scientific name: Saccharomyces Cerevisiae, manufactured by Nisshin Seifun Group, product name: Dry Yeast), 0.50% by mass of fermented cellulose (manufactured by Synaptec Co., Ltd.) as a thickener, and 20% by mass of D-glucose (manufactured by Tokyo Chemical Industry Co., Ltd., product name: G0048) were added was formed into droplets using a syringe equipped with a 32G syringe needle at atmospheric pressure, room temperature (25°C), and a rate of one drop per second, and the formed droplets were placed in a container (made of PTFE) lined with the composite particles 1 to produce liquid marble 1.

[0148] (Experimental Example 2) -Production of Composite Particle 2- As the hydrophobic solid particle A, polytetrafluoroethylene (PTFE, number average particle diameter d50a: 1.0 μm, contact angle CAa: 120°, mass Xa: 100.0 g, density Ya: 2.20 × 10 -12 g / μm 3 , volume Za: 0.52 μm 3 , c, product name: 430935-100G), and hydrophobic solid particles B, hydrophobic silica (number average particle size d50b: 0.030 μm, contact angle CAb: 170°, mass Xb: 10.6 g, density Yb: 1.80 × 10 -12 g / μm 3 , volume Zb: 1.4×10 -5 μm 3 , Shin-Etsu Chemical Co., Ltd., product name: QSG-30), and as solid particles C, hydroxypropyl cellulose (HPC) (Sigma-Aldrich, product name: 19884-100G) was finely divided (number average particle diameter d50c: 0.1 μm, contact angle CAc1: 75°, contact angle CAc2: 50°, mass Xc: 0.12 g, density Yc: 1.3 × 10 -12 g / μm 3 , volume Zc: 5.2×10 -4 μm 3) was used to add the mixture to a V-shaped container rotary mixer (manufactured by Nishimura Machinery Works, Ltd., device name: NV-5) under inert gas (nitrogen, 25°C) and stirred at 10 rpm for 12 hours to obtain composite particles 2. The volume of each particle was calculated based on the assumption that the particle was a perfect sphere with the number-average particle size as its diameter.

[0149] -Production of Liquid 2 for Liquid Marble- Liquid 2 for liquid marble was produced in the same manner as liquid 1 for liquid marble in Experimental Example 1, except that Composite Particle 1 was replaced with Composite Particle 2.

[0150] (Experimental Example 3) -Production of Liquid 3 for Liquid Marble- Liquid 3 for liquid marble was produced in the same manner as liquid 1 for liquid marble in Experimental Example 1, except that yeast was not added.

[0151] (Experimental Examples 4 to 13 and Reference Examples 1 to 4) Composite particles 4 to 17 and liquids for liquid marble 4 to 17 were produced in the same manner as in Experimental Example 1, except that the compositions and contents were changed to those shown in Tables 1-1 to 1-5 and Tables 2-1 to 2-3.

[0152] [Table 1-1]

[0153] [Table 1-2]

[0154] [Table 1-3]

[0155] [Table 1-4]

[0156] [Table 1-5]

[0157] [Table 2-1]

[0158] [Table 2-2]

[0159] [Table 2-3]

[0160] In Tables 1-3 and 1-4, "content (mass%) of hydrophobic solid particle B" is a value calculated from the following formula 4, "content 1 (mass%) of solid particle C" is a value calculated from the following formula 5, and "content 2 (mass%) of solid particle C" is a value calculated from the following formula 6. Content of hydrophobic solid particles B (mass%) = Xa / (Xa+Xb+Xc)×100 Equation 4 Content rate of solid particles C 1 (mass%) = Xc / (Xa+Xc)×100 ··· Formula 5 Content rate of solid particles C2 (mass%)=Xc / (Xa+Xb+Xc)×100...Equation 6 In the formulas 4, 5, and 6, Xa represents the mass (g) of hydrophobic solid particle A added in the production of the composite particles, Xb represents the mass (g) of hydrophobic solid particle B added in the production of the composite particles, and Xc represents the mass (g) of solid particle C added in the production of the composite particles.

[0161] Details of the materials used in the experimental and reference examples are as follows.

[0162] -Hydrophobic solid particles A- Polytetrafluoroethylene (PTFE, number average particle size d50a: 1.0 μm, contact angle CAa: 120°, density Ya: 2.20×10 -12 g / μm 3 (Sigma-Aldrich, product name: 430935-100G)

[0163] -Hydrophobic solid particles B- Hydrophobic silica (number average particle size d50b: 0.030 μm, contact angle CAb: 170°, density Yb: 1.80×10 -12 g / μm 3 , Shin-Etsu Chemical Co., Ltd., product name: QSG-30)

[0164] -Solid particle C- Micronized hydroxypropyl cellulose (HPC) (number average particle size d50c: 0.1 μm, contact angle CAc1: 75°, contact angle CAc2: 50°, mass Xc: 0.11 g, density Yc: 1.3 × 10 -12 g / μm 3 , volume Zc: 5.2×10 -4 μm 3 ) was prepared by freezing hydroxypropyl cellulose (HPC) (Sigma-Aldrich, product name: 19884-100G) by immersing it in liquid nitrogen for 10 minutes, and then pulverizing it for 15 minutes using a freeze-pulverizing device (JFC-400, Japan Analytical Industry Co., Ltd.). Each time, a small amount was taken and measured under a microscope to calculate the number-average particle size, and the process was repeated until the desired particle size was obtained (in Table 1-1, finely divided hydroxypropyl cellulose is indicated as "HPC").

[0165] -Biocatalyst- Yeast (scientific name: Saccharomyces cerevisiae, manufactured by Nisshin Seifun Group, product name: dry yeast)

[0166] -Thickener- Official honey (manufactured by Nakakita Pharmaceutical Co., Ltd.) -HPC (Sigma-Aldrich) Fermented cellulose (manufactured by Synaptec Co., Ltd.) PVP (Sigma-Aldrich)

[0167] -Second component- D-glucose (Tokyo Chemical Industry Co., Ltd., product name: G0048)

[0168] Next, the "efficiency of producing valuable materials" was evaluated as follows for Liquid Marble 1 and Liquid Marble 2 obtained in Experimental Examples 1 and 2. The results are shown in Table 3.

[0169] <Production efficiency of valuable materials> The efficiency of valuable substance production by the biocatalyst (yeast fungus) was evaluated by carrying out the following "valuable substance production evaluation" and "substrate consumption evaluation."

[0170] <<Evaluation of valuable resource production>> 10 g of the produced sample was filled into a 200 mL airtight container (product name: GL45 series, manufactured by Shibata Scientific Co., Ltd.) and then allowed to stand at 35°C under a nitrogen atmosphere for 12 hours. After standing, the container was immersed in a water bath at 70°C and allowed to stand for an additional 2 hours. Then, 100 mL of gas was collected from the container and the ethanol content was measured. The ethanol content was measured using a Kitagawa gas sampler (AP-20) and a Gastec ethanol detector tube (Ethanol 112). This measured value was taken as the production rate A (%). As a control experiment, the same amount of liquid containing the biocatalyst as that used to produce the 10 g sample was filled into a similar container, left to stand under the same conditions, and the gas was collected in the same manner to measure the ethanol content. This measurement value was taken as the production rate B (%). The difference between the production rate A and the production rate B was defined by the following formula 7 and evaluated based on the evaluation criteria. Evaluation C = Production rate A - Production rate B Equation 7

[0171] [Evaluation Criteria] 10 points: C rating of 0.05 or more 8 points: Evaluation C is 0.01 or more and less than 0.05 5 points: Rating C is greater than 0 and less than 0.01 0 points: Grade C is 0 or less

[0172] <<Substrate consumption evaluation>> 10 g of the prepared sample was filled into a 100 mL airtight container (product name: GL45 series, manufactured by Shibata Scientific Co., Ltd.), and then left to stand at 35°C under a nitrogen atmosphere for 12 hours. Liquid components were extracted from the gas phase and sample in the container, and their concentrations were measured using a refractometer, after which the amount of substrate component in the container was measured. The liquid components were extracted by exposing the sample to ethanol vapor and filtering it through a 200 μm filter to separate it into composite particles and droplets (liquid). The substrate consumption rate A before and after the reaction, including the amount of substrate supplied, was calculated from the following formula 8. Substrate consumption rate A = {(substrate mass before reaction + total amount of substrate supplied - total amount of substrate after reaction) / (substrate mass before reaction + total amount of substrate supplied)} × 100 Equation 8 As a control experiment, a similar container was filled with a liquid containing the same amount of biocatalyst as that used to produce the 10 g sample described above, and the substrate flow was supplied under the same conditions. The substance production reaction was allowed to proceed under the same conditions of temperature, atmosphere, and time. The substrate consumption rate B before and after the reaction, including the amount of substrate supplied, was calculated using the following formula 9 in the same manner as described above. Substrate consumption rate B = {(substrate mass before reaction + total amount of substrate supplied - total amount of substrate after reaction) / (substrate mass before reaction + total amount of substrate supplied)} × 100 Equation 9 The difference between the substrate consumption rate A and the substrate consumption rate B was defined by the following formula 10 and evaluated based on the evaluation criteria. Evaluation C = Substrate consumption rate A - Substrate consumption rate B Equation 10

[0173] [Evaluation Criteria] 10 points: 20 or more C's 8 points: Grade C is between 10 and 20 5 points: Rating C is greater than 0 and less than 10 0 points: Grade C is 0 or less

[0174] [Table 3]

[0175] Next, the "coalescence suppression ability" and "durability" were measured and evaluated as follows for Liquid Marbles 1 to 17 obtained in Experimental Examples 1 to 13 and Reference Examples 1 to 4. The results are shown in Tables 4-1 to 4-3.

[0176] <Evaluation of coalescence inhibition> -Rating 1- A glass petri dish with a diameter (φ) of 30 mm was washed with a neutral detergent, immersed in a saturated aqueous solution of sodium hydroxide for 8 hours or more, and then rinsed and washed with pure water. After being thoroughly dried, it was left to stand for 12 hours in a sealed container filled with hexamethylenedisilazane vapor to prepare the glass petri dish for evaluation 1. The composite particles were added to the glass petri dish for evaluation 1 so that the thickness was about 2 mm from the bottom, and 10 μL of the liquid for liquid marbles was dropped using a microsyringe while rotating and shaking at 20 rpm with a rotary shaker (manufactured by Corning Incorporated). After one minute, another 10 μL of the liquid for liquid marbles was dropped. After another minute of rotating and shaking, if the two liquid marbles had combined to form one particle, the evaluation result was given an "E", and if they had not combined, evaluation 2 was performed.

[0177] -Rating 2- Composite particles were added to a PTFE container with a diameter (φ) of 72 mm and a height (H) of 89 mm so that the thickness was approximately 50 mm from the bottom. While rotating and shaking at 200 rpm with a gyratory shaker (manufactured by Corning), the liquid for liquid marbles was dispensed at a rate of 1 drop per second in the form of droplets with a diameter of 1 mm using a dispenser (manufactured by Musashi Engineering). After 1,000 droplets were ejected, the inside of the container was visually observed. If the liquid marbles had coalesced and burst, and a film of composite particles had formed on the water surface, it was rated as "D." If no film of composite particles had formed on the water surface, further droplets were ejected. After a total of 4,000 droplets had been ejected, the inside of the container was visually observed. If the liquid marbles had coalesced and exploded, and a film of composite particles had formed on the water surface, this was rated as "C." If no composite particles had formed on the water surface, further droplets were ejected. After a total of 6,000 droplets had been ejected, the inside of the container was visually observed. If the liquid marbles had coalesced and burst, and a film of composite particles had formed on the water surface, it was rated as "B." If no film of composite particles had formed on the water surface, it was rated as "A." The evaluation scores were calculated based on the following evaluation criteria.

[0178] [Evaluation Criteria] A: 10 points B: 8 points C: 6 points D: 4 points E: 0 points

[0179] <Durability evaluation> 500 mg of the produced liquid marble was filled into a 1 mL vial, and the vial was closed to prepare a measurement sample. The measurement sample was allowed to freely fall from a height of 200 mm onto a wood block, and the inside was visually checked. This was repeated until all the liquid marbles had burst and no longer had a particle shape. The number of times all the liquid marbles had burst was taken as the measured value, and the evaluation score was calculated based on the following evaluation criteria.

[0180] [Evaluation Criteria] 11 or more times: 10 points 9 times or more and 10 times or less: 8 points 7 times or more and 8 times or less: 6 points 5 times or more and 6 times or less: 4 points 2 to 4 times: 2 points Less than once: 0 points

[0181] <Overall rating> The total score for "coalescence prevention" and "durability" was evaluated based on the following evaluation criteria. Any evaluation score of 0 was rated as "X", the lowest rating. "E" and "X" are not suitable for industrial use.

[0182] [Evaluation Criteria] A: 19 points or more and 20 points or less B: 15 points or more and 18 points or less C: 9 points or more and 14 points or less D: 7 points or more and 8 points or less E: 6 points or less

[0183] [Table 4-1]

[0184] [Table 4-2]

[0185] [Table 4-3]

[0186] Examples of aspects of the present invention include the following. <1> The present invention relates to a method for producing a viscoelastic composition comprising: The water content is 15% by mass or more and 98% by mass or less, This liquid for liquid marble is characterized by having a viscosity at 25°C of 400 mPa·s or more and 4,000 mPa·s or less. <2> The thickener content is 0.1% by mass or more. <1> This is a liquid for liquid marble described in . <3> The thickener is a polysaccharide. <1> from <2> 1. A liquid for liquid marble according to any one of the preceding claims. <4> The biocatalyst is at least one selected from the group consisting of animal cells, plant cells, microorganisms, proteins, enzymes, organelles, hormone receptors, and antibodies. <1> from <3> 1. A liquid for liquid marble according to any one of the preceding claims. <5> The above-mentioned composition further contains at least one of an additive and a physiologically active substance. <1> from <4> 1. A liquid for liquid marble according to any one of the preceding claims. <6> The above <1> from <5> The liquid marble is characterized in that the liquid for liquid marble described in any one of the above is encapsulated in external additive particles. <7> The number average particle diameter d50e of the external particles is 1 nm or more and 10 μm or less. <6> It is a liquid marble described in. <8> the external additive particles further include hydrophobic solid particles B on the surfaces of the hydrophobic solid particles A, the hydrophobic solid particle A has a contact angle CAa with water of 110° or more and 180° or less; the contact angle CAb of the hydrophobic solid particle B with water is 110° or more and 180° or less; the ratio (d50a / d50b) of the number average particle diameter d50a of the hydrophobic solid particles A to the number average particle diameter d50b of the hydrophobic solid particles B is 10 or more and 100 or less, The composite particles have a coverage CR2 represented by the following formula 2 of 50% or more and 500% or less. <7> It is a liquid marble described in.

number

number

number

number

number

[0187] 10 Composite particles 11 Hydrophobic solid particles A 12 Solid particle B [Prior art documents] [Non-patent literature]

[0188] [Non-Patent Document 1] N.Pike et al., Proc. R. Soc. Lond. B, 2002, 269, 1211-1215 [Non-Patent Document 2] J.Tian et al., Colloids and Surfaces B, Biointerfaces, 2003, 106, 187- 190

Claims

1. The method comprises the steps of: The water content is 15% by mass or more and 98% by mass or less, A liquid for liquid marbles, the surface of which is coated with particles containing a hydrophobic material, characterized in that the viscosity at 25°C is 500 mPa·s or more and 4,000 mPa·s or less.

2. 2. The liquid for liquid marble according to claim 1, wherein the content of the fermented cellulose is 0.1% by mass or more.

3. A liquid for liquid marbles described in any of claims 1 to 2, wherein the biocatalyst is at least one selected from animal cells, plant cells, microorganisms, proteins, enzymes, organelles, hormone receptors, and antibodies.

4. A liquid for liquid marble described in any one of claims 1 to 3, further containing at least one of an additive and a physiologically active substance.

5. A method for producing a composition comprising: a biocatalyst; water; and a thickener; The water content is 15% by mass or more and 98% by mass or less, A liquid for liquid marbles, the surface of which is coated with particles containing a hydrophobic material, characterized in that the viscosity at 25°C is 1,180 mPa·s or more and 3,500 mPa·s or less.

6. 6. A liquid marble comprising the liquid for liquid marble according to claim 1 , encapsulated in externally added particles.

7. The liquid marble according to claim 6, wherein the number average particle diameter d50e of the external particles is 1 nm or more and 10 μm or less.

8. the external additive particles further include hydrophobic solid particles B on the surfaces of hydrophobic solid particles A, the hydrophobic solid particle A has a contact angle CAa with water of 110° or more and 180° or less; the contact angle CAb of the hydrophobic solid particle B with water is 110° or more and 180° or less, a ratio (d50a / d50b) of a number average particle diameter d50a of the hydrophobic solid particles A to a number average particle diameter d50b of the hydrophobic solid particles B is 10 or more and 100 or less, The coverage CR expressed by the following formula 2 2 The liquid marble according to claim 7, which is a composite particle having a molecular weight of 50% or more and 500% or less. [0010] In the formula 2, Xa represents the mass (g) of the hydrophobic solid particle A, Xb represents the mass (g) of the hydrophobic solid particle B, and Ya represents the density (g / μm 3 ), Yb is the density of the hydrophobic solid particles B (g / μm 3 ), Za is the volume (μm 3 ), Zb is the volume (μm 3 )

9. the composite particle further comprises a solid particle C on a surface of the hydrophobic solid particle A, the hydrophobic solid particle A has a contact angle CAa with water of 110° or more and 180° or less; The contact angle CAc1 of the solid particle C with water is less than 110°, the contact angle CAc2 of the solid particle C with n-hexane is less than 110°, a ratio (d50a / [(d50b+d50c) / 2]) of a number average particle diameter d50a of the hydrophobic solid particles A to an average value of a number average particle diameter d50b of the hydrophobic solid particles B and a number average particle diameter d50c of the solid particles C is 10 or more and 100 or less, The coverage CR expressed by the following formula 3 3 The liquid marble according to claim 8, wherein the content of fluorine is 0.3% or more and 18% or less. [0025] In Equation 3, the coverage rate CR 1 represents a value calculated by the following formula 1, and the coverage rate CR 2 represents a value calculated by the following formula 2. [0030] In the formula 1, Xa represents the mass (g) of the hydrophobic solid particle A, Xc represents the mass (g) of the solid particle C, and Ya represents the density (g / μm 3 ), Yc represents the density of the solid particles C (g / μm 3 ), Za is the volume (μm 3 ), Zc represents the volume (μm 3 ) [0045] In the formula 2, Xa represents the mass (g) of the hydrophobic solid particle A, Xb represents the mass (g) of the hydrophobic solid particle B, and Ya represents the density (g / μm 3 ), Yb is the density of the hydrophobic solid particles B (g / μm 3 ), Za is the volume (μm 3 ), Zb is the volume (μm 3 )

10. A method for producing liquid marble, comprising the steps of: encapsulating the liquid for liquid marble according to any one of claims 1 to 5 with external additive particles to obtain liquid marble.

11. A droplet forming step of forming droplets from the liquid for liquid marble; a surface coating step of coating the liquid for liquid marble with external particles having a number average particle size of 1 nm to 10 μm; The method for producing liquid marble according to claim 10, comprising:

12. the external additive particles further include hydrophobic solid particles B on the surfaces of hydrophobic solid particles A, the hydrophobic solid particle A has a contact angle CAa with water of 110° or more and 180° or less; the contact angle CAb of the hydrophobic solid particle B with water is 110° or more and 180° or less, a ratio (d50a / d50b) of a number average particle diameter d50a of the hydrophobic solid particles A to a number average particle diameter d50b of the hydrophobic solid particles B is 10 or more and 100 or less, The coverage CR expressed by the following formula 2 2 The method for producing liquid marble according to claim 11, wherein the composite particles have a content of 50% or more and 500% or less. [0050] In the formula 2, Xa represents the mass (g) of the hydrophobic solid particle A, Xb represents the mass (g) of the hydrophobic solid particle B, and Ya represents the density (g / μm 3 ), Yb is the density of the hydrophobic solid particles B (g / μm 3 ), Za is the volume (μm 3 ), Zb is the volume (μm 3 )

13. 6. An apparatus for producing liquid marble, comprising: a liquid for liquid marble according to claim 1 ;

14. A droplet forming means for forming droplets from the liquid for the liquid marble; a surface coating means for coating the surface of the liquid for liquid marble with external particles having a number-average particle size of 1 nm to 10 μm; The liquid marble manufacturing apparatus according to claim 13, further comprising:

15. the external additive particles further include hydrophobic solid particles B on the surfaces of hydrophobic solid particles A, the hydrophobic solid particle A has a contact angle CAa with water of 110° or more and 180° or less; the contact angle CAb of the hydrophobic solid particle B with water is 110° or more and 180° or less, a ratio (d50a / d50b) of a number average particle diameter d50a of the hydrophobic solid particles A to a number average particle diameter d50b of the hydrophobic solid particles B is 10 or more and 100 or less, The coverage CR expressed by the following formula 2 2 The liquid marble manufacturing apparatus according to claim 14, wherein the composite particles have a content of 50% or more and 500% or less. [006] In the formula 2, Xa represents the mass (g) of the hydrophobic solid particle A, Xb represents the mass (g) of the hydrophobic solid particle B, and Ya represents the density (g / μm 3 ), Yb is the density of the hydrophobic solid particles B (g / μm 3 ), Za is the volume (μm 3 ), Zb is the volume (μm 3 )

16. A bioreactor comprising the liquid marble according to any one of claims 6 to 9.

17. The bioreactor according to claim 16, comprising a support means for supporting the liquid marbles.

Citation Information

Patent Citations

  • Method for producing fine particles

    JP2017160188A

  • Method for producing particle, device for producing particle, and particle

    JP2019137670A

  • Method for producing particle, and particle produced by the method and medicament

    JP2020023472A